Traceability of potential enterotoxigenic Bacillus cereus in bee-pollen samples from Argentina throughout the production process - López, Ana Claudia (2020)
Bee-pollen is a functional food sold for human and animal consumption but also is a favorable microhabitat for many spore-forming bacteria. Among them, Bacillus cereus can produce several toxins and other virulence factors, causing an emetic or diarrheal syndrome after ingestion. The study involved 36 bee-pollen samples obtained from different sampling points throughout the production process (collecting, freezing, drying, and cleaning) in Argentina. Fifty isolates of B. cereus yielded 24 different fingerprint patterns with BOX and ERIC primers. Only three fingerprint patterns were maintained throughout the production process. In contrast, others were lost or incorporated during the different steps, suggesting that cross-contamination occurred as shown by differences in fingerprint patterns after freezing, drying, and cleaning steps compared to the initial collection step. Genes encoding for cereulide (ces), cytotoxin K (cytK), sphingomyelinase (sph), the components of hemolysin BL (hblA, hblB, hblC, hblD) and non-hemolytic complex (nheAB) were studied. All the isolates displayed one or more enterotoxin genes. The most frequent virulence genes detected belong to the HBL complex, being the most abundant hblA (98%), followed by hblD (64%), hblB (54%), and hblC (32%), respectively. Ten strains (20%), present at all sampling points, carried all the subunits of the HBL complex. The non-hemolytic enterotoxic complex (nheAB) was found in 48 strains (96%), while seven strains (14%) present at all sampling points showed the amplification product for sphingomyelinase (sph). One cereulide-producer was isolated at the cleaning step; this strain contained all the components for the hemolytic enterotoxin complex HBL, the NHE complex, and cytotoxin K related to the foodborne diarrhoeal syndrome. In total, 11 different virulence patterns were observed, and also a correlation between rep-fingerprint and virulence patterns. The results suggest that bee-pollen can be contaminated at any point in the production process with potential enterotoxic B. cereus strains, emphasizing the importance of hygienic processing.